The Pearl Sac Formation in Male and Female Pinctada maxima Host Oysters Implanted With Allograft Saibo - La Eddy; Ridwan Affandi; Nastiti Kusumorini; Yulvian Sani; Wasmen Manalu (HAYATI Journal of Biosciences, 2015)
An experiment was conducted to study the effect of male and female host oysters on the pearl sac formation in Pinctada maxima oyster. One hundred sixty oysters were used in a completely randomized design with 2 x 4 factorial arrangement and 20 replications. The 1st factor was that sex of host oyster consisted of two levels that is males and females. The 2nd factor was week after nucleus implantation with four levels that is 1, 2, 3, and 4 weeks. The parameters observed were the percentage of successful oysters to form the pearl sac, the speed of pearl sac formation, the percentage of nucleus coverage by the pearl sac, histology of the pearl sac growth and development, and haemolymph glucose, calcium and phosphorus concentrations. Our results showed that the percentages of host oysters that succeeded in forming a pearl sac were 80% and 75% in female and male host oysters, respectively. There was no statistical difference in nucleus rejection and mortality in male and female host oysters but the results indicated that male host oysters showed a numerically higher nucleus rejection. The speed of pearl sac growth and the percentage of nucleus coverage by the pearl sac in female host oysters were better than those in male host oysters. Haemolymph calcium, phosphorus and glucose concentrations, oxygen consumption, and histological development of the pearl sac were not different between male and female host oysters. Pearl sac formation in the female host oysters was better than that in male host oysters.